Coagulation disorders and vascular diseases of the liver in patients with COVID-19 - Tsafaridou, Maria; Maniadaki, Ilianna; Koutroubakis, Ioannis; Samonakis, Dimitrios N. (Clinical and Experimental Hepatology, 2022)
The current coronavirus disease 2019 (COVID-19) pandemic has caused a global health emergency crisis, since its outbreak at the end of 2019. Although it mainly affects the respiratory system, it is documented that several important extrapulmonary manifestations exist in the context of the COVID-19 infection. Amongst the major pathophysiological mechanisms, the generation of a prothrombotic environment is increasingly recognized and is related to thromboembolic events. We conducted a review of the literature and summarized the coagulation disorders in the liver in patients with COVID-19.